Transparent Thin Film of Zinc Zirconate Deposited by DC Magnetron Sputtering Technique - Khottummee, Nattee; Sumphao, Theerawut; Thaowankaew, Somporn (Creative Science, 2020)
ZnZrO3 thin film was deposited by the non-reactive DC magnetron sputtering technique on glass substrates using ZnO and ZrO2 composite target of with a mass ratio of 90:10. The composited target was pressed at a pressure of 25 MPa. The deposition process was operated with the non-reactive method and heat treatment film in the air at a temperature of about 400 ̊C for 1 h. The X-ray diffraction patterns revealed cubic perovskite phases of ZnZrO3. The surface morphology was observed distribution of nano-granular and thickness of about 231 nm. The ZnZrO3 thin film was exhibited high transparency of about 95.46% in the visible region and optical gap energy of about 3.27 eV. The results of this research promise can develop transparent film for solar cell applications in the future.